Civilizar religiões (Revista Eletrônica Estudos Hegelianos, 2018)
This article deals with the conflict between, on the one hand, religious identity’ intentions of absolute validity and, on the other, the modern view of the state as it presents itself historically as ‘wordly God‘. At first, it argues against the Kantian view of a rational religion which would justify the diverse historical religions only inasmuch as they ceased to be what they are. It is suggested, thus, that the modern state and the many (civil) religions possess each adequate spaces where they could ‘civilize‘ themselves, e.g. the state by means of Right, religion by means of a disposition of the soul akin to modern times, in which the separation of state and religious authority is recognized and respected. The very instable character of this modern arrangement is thus analyzed with recourse to Aeschylus’ Eumenides and Hegel’s Philosophy of Right.